2007
DOI: 10.1172/jci31726
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress downregulates epidermal antimicrobial peptide expression and increases severity of cutaneous infections in mice

Abstract: The skin is the first line of defense against microbial infection, and psychological stress (PS) has been shown to have adverse effects on cutaneous barrier function. Here we show that PS increased the severity of group A Streptococcus pyogenes (GAS) cutaneous skin infection in mice; this was accompanied by increased production of endogenous glucocorticoids (GCs), which inhibited epidermal lipid synthesis and decreased lamellar body (LB) secretion. LBs encapsulate antimicrobial peptides (AMPs), and PS or syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
187
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(198 citation statements)
references
References 83 publications
(132 reference statements)
6
187
0
5
Order By: Relevance
“…By day 7 following wounding, 85.4% of restraint-stress mice had bacterial counts predictive of infection, compared to 27.4% of controls 32 . In accord with these data, other researchers have also found that stress impairs the skin's barrier function, resulting in increased severity of cutaneous infections in mice 33 .…”
Section: Stress and Wound Healingsupporting
confidence: 69%
“…By day 7 following wounding, 85.4% of restraint-stress mice had bacterial counts predictive of infection, compared to 27.4% of controls 32 . In accord with these data, other researchers have also found that stress impairs the skin's barrier function, resulting in increased severity of cutaneous infections in mice 33 .…”
Section: Stress and Wound Healingsupporting
confidence: 69%
“…In addition, acute cold stress was shown to induce a significant release of -defensin in the jejunum in this study, supporting the possibility that stress might affect this protective pathway in the gut, as have been shown in the skin. 110 Furthermore, we have also found that cold stress evoked a differential gender-determined increase in human intestinal macromolecular permeability. 111 This enhanced permeability could lead to excessive uptake of luminal antigens and bacterial products that may initiate an inflammatory response in the mucosa.…”
Section: Permeabilitymentioning
confidence: 64%
“…Psychological stress decreased epidermal cell proliferation, adversely effected differentiation and decreased the size and density of corneodesmosomes, all of which negatively impact barrier function (47). Stress decreased antimicrobial peptides in the epidermis (animal model), an effect which resulted in more severe skin infections (48).…”
Section: Discussionmentioning
confidence: 99%